The Profile of Oral and Dental Health of Children in the Agroindustrial Environment in Jember - Berlian Prihatiningrum; Niken Probosari; Sulistiyani Sulistiyani; Dyah Setyorini; Roedy Budirahardjo; Sukanto Sukanto (Health Notions, 2022)
Oral and dental health is one of the important components to improve a person's quality of life. The aim of this study is to describe the oral and dental health status in Children who lived In Agroindustrial environment in Jember. This study was an analytical descriptive research. The subjects used were 255 students in 3 elementary schools. The sampling technique used was total population sampling. Data obtained by questionnaire and direct examination in the form of examination of DMF-t or def-t index and oral hygiene index. Then the data tabulation was carried out using table. Based on the caries index, it shows that children in the coffee and cocoa agro-industry environment had a low category caries in permanent teeth (mean DMF-t = 1,6), mean while in deciduous teeth included in the moderate category caries (mean def-t = 4,11). The profile of oral and dental health status in Children who lived in agroindustrial environment need to improve. Keywords: oral health status; agroindustrial environtment; children